VD_FINDINFO Jug / 2025 / 374 vom 3. April 2025 - VD Tribunal cantonal (2025)
VIOLENCE CONTRE LES AUTORITÉS, PRÉSOMPTION D'INNOCENCE, SURSIS À L'EXÉCUTION DE LA PEINE | 285 ch. 1 CP, 40 CP, 41 CP, 42 CP, 47 CP